Volatile constituents of roasted tigernut oil (Cyperus esculentus L.). - Lasekan, Ola (Wiley, 2013)
BACKGROUND: Volatile compounds play a key role in determining the sensory appreciation of vegetable oils. In this study a systematic evaluation of odorants responsible for the characteristic flavour of roasted tigernut oil was carried out.